Design of Cashew Marketing Strategy Through Evaluation of Export Potential to Enter the Global Market (Case Study of Mrs. Tini's MSMEs in Ciputat) - Revikhansyah, Thiersyanda (Riviera Publishing, 2024)
This study aims to identify market expansion opportunities and address the administrative barriers MSMEs Kacang Mete Bu Tini face in exporting fresh or dried shelled cashew nuts with HS Code 080132 to Malaysia and Thailand. MSMEs Kacang Mete Bu Tini encounter significant administrative obstacles due to the lack of essential export documents such as quality certificates, certificates of origin, etc. These obstacles slow the market expansion and reduce the product's competitiveness in international markets. The research conducted through Revealed Comparative Advantage (RCA) analysis shows that Indonesian cashew nuts have significant comparative advantages in the Malaysian and Thai markets, with RCA values reaching 3.318911 in Malaysia and 2.556656 in Thailand. An RCA value greater than one indicates a comparative advantage in both markets. Regarding competitive advantage, Malaysia holds a